The Impact of Mineral and Energy Supplementation and Phytogenic Compounds on Rumen Microbial Diversity and Nitrogen Utilization in Grazing Beef Cattle - Teobaldo, Ronyatta Weich [UNESP]; Granja-Salcedo, Yury Tatiana; Cardoso, Abmael da Silva; Constancio, Milena Tavares Lima [UNESP]; Brito, Thais Ribeiro [UNESP]; Romanzini, Eliéder Prates [UNESP]; Reis, Ricardo Andrade [UNESP] (MDPI, 2023)
The objective of this study was to evaluate the effect of the addition of a phytogenic compound blend (PHA) containing hydrolyzable tannins, carvacrol, and cinnamaldehyde oil to mineral salt or energy supplementation on the rumen microbiota and nitrogen metabolism of grazing Nellore cattle. Eight castrated Nellore steers were distributed in a double-Latin-square 4 × 4 design, with a 2 × 2 factorial arrangement (two types of supplements with or without the addition of the PHA), as follows: energy supplement without the PHA addition (EW); energy supplement with the PHA addition (EPHA); mineral supplement without the addition of the PHA (MW); mineral supplement with the PHA addition (MPHA). Steers that received supplements with the PHA have a lower ruminal proportion of valerate (with the PHA, 1.06%; without the PHA, 1.15%), a lower ruminal abundance of Verrucomicrobia, and a tendency for lower DM digestibility (with the PHA, 62.8%; without the PHA, 64.8%). Energy supplements allowed for higher ammonia concentrations (+2.28 mg of NH3-N/dL), increased the propionate proportion (+0.29% of total VFA), and had a higher ruminal abundance of Proteobacteria and Spirochaetae phyla in the rumen. The PHA addition in the supplement did not improve nitrogen retention, reduced the ruminal proportion of valerate, and had a negative impact on both the total dry-matter digestibility and the abundance of several ruminal bacterial groups belonging to the Firmicutes and Verrucomicrobia phyla.
Keywords: digestibility; essential oils; hydrolyzable tannins; rumen fermentation; ruminal bacteria